Quick-dry transparent super-hydrophobic and oleophobic coating suitable for photovoltaic panel and preparation method of quick-dry transparent super-hydrophobic and oleophobic coating

By using a specific formula of quick-drying transparent superhydrophobic oleophobic coating, the problems of complex self-cleaning coating of existing photovoltaic glass panels and strict film formation and curing conditions are solved, and the combination of high transmittance and self-cleaning performance is achieved, and the power generation efficiency and economic benefits of photovoltaic panels are improved.

CN119614027APending Publication Date: 2025-03-14ELECTRIC POWER RES INST OF GUANGXI POWER GRID CO LTD

Patent Information

Application Number
CN202411413160.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing photovoltaic glass panel self-cleaning coating requires complex pretreatment and construction processes, and there are specific requirements for the coating film-forming and curing conditions, making it difficult to achieve a combination of high transmittance and excellent surface self-cleaning performance.

Method used

A quick-dry transparent superhydrophobic oleophobic coating including hydrophobic vapor-phase nanosilica, hexafluoropropylene dimer, tetrafluoroethyl ether and other components is used to form a coating with high transmittance and self-cleaning properties through specific formulations and preparation methods.

Benefits of technology

The long-term cleanliness of photovoltaic panel surfaces is achieved, high power generation level is maintained, the construction process is simplified, the preparation cost is reduced, and the labor cost of manual cleaning is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614027A_ABST
    Figure CN119614027A_ABST
Patent Text Reader

Abstract

The invention discloses a quick-dry transparent super-hydrophobic and super-oleophobic coating suitable for a photovoltaic panel and a preparation method of the quick-dry transparent super-hydrophobic and super-oleophobic coating, and belongs to the technical field of new materials. The invention provides a quick-dry transparent super-hydrophobic and oleophobic coating. The quick-dry transparent super-hydrophobic and oleophobic coating comprises nano-scale hydrophobic silicon dioxide particles and a fluorine-containing acrylate polymer, through reasonable design and combination of the nanoparticles and the polymer, the super-hydrophobic and oleophobic coating with high visible light transmittance and excellent self-cleaning performance is obtained. The coating can ensure the cleanliness of glass on the surface of the photovoltaic panel in a long time, is hydrophobic and oleophobic, keeps a high sunlight incidence rate, and improves the power generation level; meanwhile, the preparation process of the coating is simple and convenient, the flow is simple, the curing and film forming time is short, and the cost waste caused by complex procedures and manual maintenance and cleaning is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and in particular relates to a quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels and a preparation method thereof. Background Art

[0002] Photovoltaic power generation, as a representative of emerging green energy, has been widely developed in recent years and is expected to reduce greenhouse gas emissions caused by thermal power generation. As the main light energy intake interface of photovoltaic power generation components, the light transmittance of photovoltaic glass panels directly affects the power generation efficiency of the entire component. This drives the provision of effective strategies to solve the problem of reduced solar energy utilization efficiency caused by low transmittance due to surface contamination of photovoltaic panels. For example, oil stains, water stains, and the adhesion of sand and dust will pollute the surface of photovoltaic panels, resulting in a decrease in the actual light energy intake of photovoltaic components and a decrease in power generation. In addition, the high labor cost caused by the cleaning of photovoltaic panels is also one of the factors affecting economic benefits.

[0003] CN202211533960.5 discloses a photovoltaic self-cleaning dustproof and anti-reflective nano coating and its use method, wherein the nano material includes the following components: amorphous silicon dioxide, deionized water, polyethanol and surfactant. First, silicon dioxide is placed in deionized water for heating, stirring and mixing to obtain a suspension, and then the polyethanol and surfactant mixed solution is added to the above suspension, and after complete mixing, the mixture is cooled to obtain the final coating product. This coating is suitable for surfaces such as photovoltaic glass and photovoltaic panels. Through the action of the nano coating, the surface has the functions of self-cleaning, dustproof and anti-reflective, and effectively protects the glass surface and improves the power generation efficiency.

[0004] CN201910221706.3 discloses a coating method for photovoltaic self-cleaning glass, after a certain amount of tetrabutyl titanate, sodium octadecanoate and anhydrous ethanol are mixed, applied to the cleaned glass surface, and then calcined at high temperature to form a nanostructured TiO2 film on the glass surface. The coating method of the present invention is simple to operate, easy to use, has good coating effect, and has good film adhesion. Compared with the existing sol-gel technology, nano TiO2 has better dispersibility based on the heat dissipation effect of high temperature; after high temperature treatment, the stability of TiO2 structure is better; the coating process does not require clean room and atmosphere protection; through the photo-induced superhydrophilicity and photocatalytic properties of nano TiO2 film, a water film is formed on the glass surface to isolate pollutants from attaching, degrade organic pollutants, and have self-cleaning properties; the finished product after coating is used in photovoltaic power stations, so that the labor cost of its operation and maintenance is effectively reduced, and the power generation system efficiency of the power station is higher, which can be increased by about 2 to 5%.

[0005] However, the self-cleaning coatings for photovoltaic glass panels reported so far all require complex pretreatment and construction processes, and have specific requirements for the film-forming and curing conditions of the coatings. Therefore, it is still a challenge to prepare a coating that has high transmittance and excellent surface self-cleaning properties and can be easily constructed and quickly formed. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions, wherein the coating, in terms of mass percentage, comprises:

[0010] 4-5wt% hydrophobic fumed nano-silica; 24-25wt% hexafluoropropylene dimer; 55-65wt% tetrafluoroethyl ether; 0.5-3wt% methyl methacrylate; 1-2wt% hydroxyethyl methacrylate; 6-10wt% perfluorooctyl ethyl acrylate; 2-3.5wt% allyl alcohol glycidyl ether; 0.1wt% azobisisobutyronitrile; 0.2wt% perfluorooctyl ethyl iodide; 1wt% isobornyl acrylate.

[0011] As a preferred embodiment of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels of the present invention, the coating, in terms of mass percentage, comprises:

[0012] 4-5wt% hydrophobic fumed nano-silica; 24.5wt% hexafluoropropylene dimer; 55wt% tetrafluoroethyl ether; 2wt% methyl methacrylate; 1-2wt% hydroxyethyl methacrylate; 6-10wt% perfluorooctyl ethyl acrylate; 2-3.5wt% allyl alcohol glycidyl ether; 0.1wt% azobisisobutyronitrile; 0.2wt% perfluorooctyl ethyl iodide; 1wt% isobornyl acrylate.

[0013] As a preferred embodiment of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels of the present invention, the coating, in terms of mass percentage, comprises:

[0014] 4.5wt% hydrophobic fumed nano-silica; 24.5wt% hexafluoropropylene dimer; 55wt% tetrafluoroethyl ether; 2wt% methyl methacrylate; 1.7wt% hydroxyethyl methacrylate; 8wt% perfluorooctyl ethyl acrylate; 3wt% allyl alcohol glycidyl ether; 0.1wt% azobisisobutyronitrile; 0.2wt% perfluorooctyl ethyl iodide; 1wt% isobornyl acrylate.

[0015] As a preferred embodiment of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels described in the present invention, the particle size of the hydrophobic gas-phase nano-silica is 5 to 40 nm.

[0016] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels.

[0017] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0018] Hydrophobic fumed nano-silica is dispersed in hexafluoropropylene dimer, and wet-milled after continuous stirring, and then ultrasonicated for 8 to 15 minutes to obtain solution A;

[0019] Methyl methacrylate, hydroxyethyl methacrylate, perfluorooctyl ethyl acrylate, and allyl alcohol glycidyl ether are dissolved in tetrafluoroethyl ether, and stirred continuously until fully dissolved to obtain solution B;

[0020] Solution A is slowly added to solution B with continuous stirring, azobisisobutyronitrile is slowly added and stirred for reaction for 10 to 20 minutes, perfluorooctyl ethyl iodide and isobornyl acrylate are added dropwise, and stirring is continued for reaction for 4.5 to 6 hours to obtain a quick-drying transparent super hydrophobic and oleophobic coating.

[0021] As a preferred solution of the method for preparing the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to the present invention, hexafluoropropylene dimer is appropriately added during the wet grinding process to keep the total volume of the solvent unchanged.

[0022] As a preferred embodiment of the method for preparing the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to the present invention, the continuous stirring comprises the following steps: the stirring speed is 550 to 700 rpm and the stirring time is 5 to 30 min.

[0023] As a preferred embodiment of the method for preparing the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to the present invention, the stirring reaction comprises the following steps: the stirring speed is 600 to 800 rpm and the stirring temperature is 30 to 40°C.

[0024] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide an application of a quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels.

[0025] In order to solve the above technical problems, the present invention provides the following technical solutions, including:

[0026] The quick-drying transparent super hydrophobic and oleophobic coating and the fluorinated curing agent are mixed and stirred for 5 to 15 minutes, and then applied to the surface of the photovoltaic panel. After curing for 3 to 8 minutes, a quick-drying transparent super hydrophobic and oleophobic coating is formed on the surface of the photovoltaic panel.

[0027] As a preferred solution for the application of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to the present invention, the preparation method of the fluorinated curing agent comprises:

[0028] In a nitrogen atmosphere, hexamethylene diisocyanate trimer is added to butyl acetate, and after stirring for 20 to 40 minutes, perfluorohexylethyl alcohol is added dropwise for 20 to 40 minutes, and then the system is heated to 55 to 65°C, and stirring is continued for 1 to 3 hours, and then the final product is subjected to low-pressure rotary evaporation to remove the ethyl acetate solvent to obtain a fluorinated curing agent;

[0029] Wherein, the mass ratio of the hexamethylene diisocyanate trimer to perfluorohexylethyl alcohol is 2-3:1.5-2.5.

[0030] As a preferred solution for the application of the quick-drying transparent super-hydrophobic and oleophobic coating suitable for photovoltaic panels of the present invention, the coating includes coating on the surface of the photovoltaic panel by roller coating, and the roller needs to be fully immersed in the coating during the roller coating process, and the coating is applied to the surface of the photovoltaic panel by a single roller coating method. It also includes spraying, dipping and other methods.

[0031] Beneficial effects of the present invention:

[0032] (1) The quick-drying transparent super-hydrophobic and oleophobic coating prepared by the present invention has excellent super-hydrophobic and oleophobic properties, which can prevent the accumulation of water stains and oil stains on the surface of photovoltaic components during long-term service, keep the surface of photovoltaic panels clean for a long time, and enable photovoltaic panels to maintain a high level of power generation.

[0033] (2) The quick-drying transparent super-hydrophobic and oleophobic coating has excellent surface self-cleaning properties. When solid pollutants adhere to the surface of the photovoltaic panel, on the one hand, the chemical properties of the coating surface can reduce the interaction force at the interface, allowing them to fall off from the surface of the photovoltaic panel under their own gravity or slight external force (such as wind); on the other hand, the coating's excellent super-hydrophobic and oleophobic properties can repel most liquids, allowing solid pollutants to be washed away under rain conditions, and there is no water stain left on the coating surface, ensuring that the photovoltaic panel can maintain a clean surface for a long time, while reducing the labor cost caused by regular manual cleaning and improving economic benefits.

[0034] (3) The quick-drying transparent super hydrophobic and oleophobic coating is a single-component coating that is easy to apply. In addition to the roller coating process, it can also be applied to the surface of the photovoltaic panel by spraying, dipping, and other methods. In addition, its curing film formation time is fast and no high-temperature curing is required, which greatly simplifies the construction process and reduces the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0036] Figure 1 This is a rating scale for tape peel testing based on ASTM D3359.

[0037] Figure 2 This is a real photo of a quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels sprayed on the surface of a photovoltaic panel, wherein the left side is the original panel without spraying, and the right side (red frame area) is the panel coated with the coating.

[0038] Figure 3 The figure is a comparison curve of the transmittance in the visible light region between the coating-glass prepared in Example 1 of the present invention and the original glass.

[0039] Figure 4 This is a Fourier transform infrared spectrum (FT-IR) curve of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels prepared in Example 1 of the present invention after drying.

[0040] Figure 5 The nuclear magnetic hydrogen spectrum (H NMR) of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels prepared in Example 1 of the present invention 1 -NMR) spectrum.

[0041] Figure 6These are optical photographs of the static water contact angle and oil contact angle of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels prepared in Example 1 of the present invention.

[0042] Figure 7 This is an anti-fouling image of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0045] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0046] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0047] The coating prepared in the embodiment of the present invention was characterized and tested as follows:

[0048] Fourier transform infrared spectroscopy analysis: The infrared transmittance of the coating samples was analyzed using a NicoletiS 50 Fourier transform infrared spectrometer.

[0049] Nuclear magnetic resonance (NMR) spectrometer was used to analyze the coating samples.

[0050] The coating prepared in the embodiment of the present invention was tested for performance as follows:

[0051] Visible light transmittance: The transmittance of the samples (coated-glass and original glass) to visible light was tested using a Shimadzu UV 3600 UV-visible spectrophotometer. The size of the test sample was 7.5 cm × 2.5 cm, and a glass slide of the same size was selected as a control sample during the test. The transmittance of air was set as the baseline for the test. The test wavelength range was 400 nm to 800 nm.

[0052] Contact angle: The contact angle of water droplets / oil droplets (if not otherwise specified, the oils used in the test here are all gasoline, i.e., a mixture of aliphatic hydrocarbons and cycloalkanes) on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For the measurement of the contact angle in a non-moving state, a water droplet / oil droplet (~10 μL) was first added to the sample surface by a motor-controlled syringe. When the droplet is stable, a side image is taken with a camera, and the software is used for fitting calculation to obtain the static contact angle value of the water droplet / oil droplet on the coating surface.

[0053] Rolling / sliding angle: The sliding angle of water / oil droplets on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For sliding angle measurement, a motor-controlled rotatable test platform is used to tilt the sample, and the rotation angle of the platform is displayed in real time on a computer connected to the motor. At the beginning of the test, the initial inclination angle of the platform is maintained at 0°. After a water / oil droplet (~10μL) is added to the coating surface via a syringe, the motor is controlled to rotate the platform. The rotation stops at the moment the droplet begins to roll on the surface, and the rotation angle displayed on the computer is recorded as the rolling angle. Each sample is measured at three different positions to reduce data errors.

[0054] Coating adhesion test: Tape peeling test is used as the coating adhesion test method, according to ASTMD3359 standard, the grade rating table is as follows Figure 1 All test samples were cross-cut with a 1mm interval using a grating knife. Then 3M TM 600 tape is attached to the surface of the cut area and pressed with a load of 2kg to make the tape fully contact the test area. After standing still for 90 seconds, the tape is quickly pulled apart in the vertical direction (90°). The same area is tested twice. The remaining part of the coating on the substrate is then observed to evaluate the adhesion of the coating.

[0055] Example 1

[0056] This embodiment provides a method for preparing a quick-drying transparent super-hydrophobic and oleophobic coating, specifically:

[0057] The formula of the quick-drying transparent super hydrophobic and oleophobic coating is: 4.5wt% hydrophobic gas-phase nano-silica; 24.5wt% hexafluoropropylene dimer; 55wt% tetrafluoroethyl ether; 2wt% methyl methacrylate; 1.7wt% hydroxyethyl methacrylate; 8wt% perfluorooctyl ethyl acrylate; 3wt% allyl alcohol glycidyl ether; 0.1wt% azobisisobutyronitrile; 0.2wt% perfluorooctyl ethyl iodide; 1wt% isobornyl acrylate.

[0058] (1) 4.5 g of hydrophobic fumed nano-silica was dispersed in 24.5 g of hexafluoropropylene dimer, and stirred at 550 rpm for 30 min at room temperature. The mixture was then placed in an agate mortar for wet grinding. During the wet grinding process, hexafluoropropylene dimer was appropriately added to ensure that the volume remained unchanged. After 30 min of wet grinding, the solution was transferred to an ultrasonic water bath for ultrasonication and was recorded as "Solution A".

[0059] (2) 2 g of methyl methacrylate, 1.7 g of hydroxyethyl methacrylate, 8 g of perfluorooctyl ethyl acrylate, and 3 g of allyl alcohol glycidyl ether were dissolved in 55 g of tetrafluoroethyl ether, and the mixture was stirred at 700 rpm for 5 min at room temperature until fully dissolved, thereby obtaining a solution B.

[0060] (3) Solution A was slowly added to solution B, and the mixture was stirred for 5 min. Then, 0.1 g of azobisisobutyronitrile was added dropwise. The mixture was placed in a constant temperature water bath at 35°C and stirred at 700 rpm for 15 min. Then, 0.2 g of perfluorooctylethyl iodide and 1 g of isobornyl acrylate were added dropwise. The mixture was stirred for 5 h to obtain a quick-drying transparent super hydrophobic and oleophobic coating.

[0061] (4) In a nitrogen atmosphere, 2.2 g of hexamethylene diisocyanate trimer was added to butyl acetate. After stirring for 30 min, 2.4 g of perfluorohexylethyl alcohol was added dropwise for 30 min. The system was then heated to 60 °C and stirred for 2 h. The final product was then subjected to low-pressure rotary evaporation to remove the ethyl acetate solvent. The obtained product was recorded as a fluorinated curing agent.

[0062] (5) After the photovoltaic panel is rinsed twice with anhydrous ethanol and deionized water alternately, ensuring that there is no dust on the surface of the photovoltaic panel, after it is completely dried, the quick-drying transparent super-hydrophobic and oleophobic coating and the fluorinated curing agent are mixed and stirred for 10 minutes, and then applied to the surface of the photovoltaic panel by roller coating. During the roller coating process, the roller needs to be fully immersed in the coating, and the photovoltaic panel surface is applied by a single roller coating method. After the roller coating is completed, the photovoltaic panel is cured at room temperature for 5 minutes, and a quick-drying transparent super-hydrophobic and oleophobic coating is prepared on the surface of the photovoltaic glass panel.

[0063] Figure 2 The quick-drying transparent super-hydrophobic and oleophobic coating suitable for photovoltaic panels prepared in Example 1 of the present invention is sprayed on a photovoltaic cell panel, wherein the left half is the original sample without spraying the coating, and the right half is the sample sprayed with the quick-drying transparent super-hydrophobic and oleophobic coating (red framed area). It can be seen that there is no difference in the photovoltaic cell panel before and after spraying, indicating that the coating has a high transparency.

[0064] Figure 3This is a comparison curve of the transmittance of the coating-glass and the original glass in the visible light region. It can be seen that the transmittance of the glass sample after spraying in the visible light region is comparable to that of the original control glass sample, indicating that the coating has an extremely high visible light transmittance.

[0065] like Figure 4 The Fourier transform infrared spectrum shows that the quick-drying transparent super hydrophobic and oleophobic coating is a thin film formed by curing the acrylic ester copolymer after drying, in which 1051cm -1 The peak at 1199 cm is the stretching vibration peak of the COC bond in the fatty chain. -1 and 1144cm -1 The peak at 1738 cm is the stretching vibration peak of the CF bond. -1 The stretching vibration peak of C=O bond is 2960cm -1 The stretching vibration peak of -CH3 is at 3300cm -1 The stretching vibration peak of -OH is at , indicating that the main component of the coating that is finally cured into a film is perfluorooctyl ethyl acrylate polymer, which can provide excellent hydrophobic and oleophobic properties. Figure 5 ) also verified this point. The characteristic peaks at 5.96ppm, 4.31ppm and 1.62ppm are all attributed to perfluorooctyl ethyl acrylate. After the coating is sprayed on the surface of the photovoltaic panel glass, due to the roughness of the photovoltaic panel glass itself, combined with hydrophobic nano-silica and perfluoroacrylate polymer, the panel glass shows excellent super-hydrophobic properties, and its static contact angle of water droplets can reach 152.79°( Figure 6 Left), the static contact angle of the oil drop can reach 81.20° ( Figure 6 Right). The coating has a certain degree of repellency against common oil stains in life, such as Figure 7 As shown, the coating has good anti-adhesion properties to edible oil, diesel and gasoline, etc.

[0066] Example 2

[0067] The difference between this embodiment and embodiment 1 is that the addition amount of hydrophobic gas-phase nano-silica is adjusted to 5g, that is, the hydrophobic gas-phase nano-silica in the coating accounts for 5wt%, and the rest of the preparation process is the same as that of embodiment 1, and a quick-drying transparent super hydrophobic and oleophobic coating is obtained.

[0068] Example 3

[0069] The difference between this embodiment and embodiment 1 is that the addition amount of hydrophobic gas-phase nano-silica is adjusted to 4g, that is, the hydrophobic gas-phase nano-silica in the coating accounts for 4wt%, and the rest of the preparation process is the same as that of embodiment 1, and a quick-drying transparent super hydrophobic and oleophobic coating is obtained.

[0070] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.

[0071] Table 1

[0072]

[0073]

[0074] As shown in the table, the addition amount of hydrophobic gas-phase nano-silicon dioxide is different, which will affect the hydrophobic and oleophobic properties of the prepared coating. When the addition amount of hydrophobic gas-phase nano-silicon dioxide increases, as in Example 2, the roughness of the final coating surface will be caused to rise, and a richer air layer can be stored after the liquid contacts the coating surface, increasing hydrophobicity. However, according to Snell's law, light is more likely to refract between two media, and due to the increase of hydrophobic gas-phase nano-silicon dioxide, more nanoparticles will be produced in the unit volume inside the coating, and the increase of surface roughness will cause two-phase interface (resin / silicon dioxide interface and resin / air interface) to be produced, and the overall refractive index of the final coating is improved, causing transmittance to decrease. And when the addition amount of hydrophobic gas-phase nano-silicon dioxide is reduced, as in Example 3, the roughness of the surface decreases, the liquid increases in contact area with the coating surface, and the interaction force is enhanced, and the corresponding hydrophobic and oleophobic properties also decrease. But the introduction of a relatively small amount of silicon dioxide can maintain a relatively high transmittance to a certain extent.

[0075] After testing, the average transmittance of the coatings prepared in Example 2 and Example 3 in the visible light region was approximately 90.3% and 91.5%, respectively. This is considered to be due to the change in the refractive index inside and on the surface of the coating caused by the change in the amount of hydrophobic gas-phase nano-silica added, but the coating still has a certain hydrophobic and oleophobic effect.

[0076] According to the results in the above table, the best technical effect can be obtained when the addition amount of the hydrophobic fumed nano-silica in the present invention is 4.5wt%.

[0077] Example 4

[0078] The difference between this embodiment and Example 1 is that the mass ratio of perfluorooctyl ethyl acrylate to methyl methacrylate, hydroxyethyl methacrylate and allyl alcohol glycidyl ether is increased to 10g, and the rest of the preparation process is the same as that of Example 1 to obtain a quick-drying transparent super hydrophobic and oleophobic coating.

[0079] Example 5

[0080] The difference between this embodiment and embodiment 1 is that the mass ratio of perfluorooctyl ethyl acrylate to methyl methacrylate, hydroxyethyl methacrylate and allyl alcohol glycidyl ether is reduced to 6g, and the rest of the preparation process is the same as that of embodiment 1 to obtain a quick-drying transparent super hydrophobic and oleophobic coating.

[0081] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.

[0082] Table 2

[0083] Example 1 Example 4 Example 5 Visible light transmittance / % 91.2 91.4 91.1 Oil contact angle / ° 81.20 87.37 78.63 Oil sliding angle / ° 2.04 2.19 3.66 Water contact angle / ° 152.79 156.93 150.61 Water rolling angle / ° 3.96 3.81 5.12 Adhesion test level 5B 4B 5B

[0084] As can be seen from the above table, the addition of perfluorooctyl ethyl acrylate in the preparation process of polymer phase in step (2) will affect the hydrophobic and oleophobic effect of coating to a certain extent. When the addition of perfluorooctyl ethyl acrylate increases, as in Example 4, fluorine-containing elements can greatly reduce the surface free energy of coating, and it has non-polar chemical properties, can reduce the interaction force with various liquids, so that the coating surface can repel liquid, showing that the contact angles of water and oil have risen respectively, 4.17 ° and 6.14 °. But correspondingly, the increase of perfluorooctyl ethyl acrylate content can cause the adhesion of coating to substrate to weaken, so that its adhesion test grade is reduced to 4B grade. And when the addition of perfluorooctyl ethyl acrylate is reduced, as in Example 5, the hydrophobic and oleophobic properties of coating are all weakened, and the water contact angle can only reach 150.61 °.

[0085] According to the results in the above table, the best technical effect can be obtained when the addition amount of perfluorooctyl ethyl acrylate in the present invention is 8wt%.

[0086] Example 6

[0087] The difference between this embodiment and embodiment 1 is that the addition amount of allyl alcohol glycidyl ether is adjusted to 3.5 g, and the addition amount of hydroxyethyl methacrylate is adjusted to 2 g, and the rest of the preparation process is the same as that of embodiment 1, and a quick-drying transparent super hydrophobic and oleophobic coating is obtained.

[0088] Example 7

[0089] The difference between this embodiment and embodiment 1 is that the addition amount of allyl alcohol glycidyl ether is adjusted to 2 g, the addition amount of hydroxyethyl methacrylate is adjusted to 1 g, and the rest of the preparation process is the same as that of embodiment 1 to prepare a quick-drying transparent super hydrophobic and oleophobic coating. The performance test of the material prepared in the above embodiment is carried out, and the comparison results with those in embodiment 1 are shown in Table 3.

[0090] Table 3

[0091] Example 1 Example 6 Example 7 Visible light transmittance / % 91.2 91.0 91.3 Oil contact angle / ° 81.20 80.01 82.36 Oil sliding angle / ° 2.04 2.76 2.54 Water contact angle / ° 152.79 150.26 154.38 Water sliding angle / ° 3.96 4.06 3.81 Adhesion test level 5B 5B 3B

[0092] As can be seen from the above table, the content of allyl alcohol glycidyl ether and hydroxyethyl methacrylate in step (2) can affect the adhesion of the coating. Since the adhesion of the coating mainly depends on the hydroxyl generated after the reaction of hydroxyethyl methacrylate and allyl alcohol glycidyl ether and the substrate to form hydrogen bonds, it is adhered together by the hydrogen bonding force. When the addition amount of allyl alcohol glycidyl ether and hydroxyethyl methacrylate increases, as in Example 6, the cross-linking strength inside the coating and the exposure of hydrogen bonds at the coating interface increase, and the adhesion after the coating film formation can be improved, but the exposure of too many polar groups can weaken the hydrophobic and oleophobic properties of the coating to a certain extent. On the contrary, when the addition amount of allyl alcohol glycidyl ether and hydroxyethyl methacrylate is reduced, the adhesion of the coating will be reduced, and the coating will fall off more seriously during the test, and it can only reach 3B grade, because the reduction of allyl alcohol glycidyl ether and hydroxyethyl methacrylate will lead to the reduction of the exposure of the coating surface hydroxyl, and the hydrophobic and oleophobic properties are slightly increased.

[0093] In summary, the preferred addition amounts of allyl alcohol glycidyl ether and hydroxyethyl methacrylate are 3 wt % and 1.7 wt %, respectively.

[0094] Comparative Example 1

[0095] The difference between this example and Example 1 is that the amount of hydrophobic gas-phase nano-silica added in the preparation step (1) in this comparative example is increased to 2.5 g, and the rest of the preparation process is the same as that in Example 1 to obtain a coating.

[0096] Comparative Example 2

[0097] The difference between this example and Example 1 is that the total amount of solvent (hexafluoropropylene dimer and tetrafluoroethyl ether) in the preparation steps (1) and (2) in this comparative example is reduced, and the rest of the preparation process is the same as that in Example 1 to obtain a coating.

[0098] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 4.

[0099] Table 4

[0100] Example 1 Comparative Example 1 Comparative Example 2 Visible light transmittance / % 91.2 85.4 88.7 Oil contact angle / ° 81.20 88.21 80.36 Oil sliding angle / ° 2.04 5.17 3.63 Water contact angle / ° 152.79 159.31 151.35 Water sliding angle / ° 3.96 3.54 3.73 Adhesion test level 5B 4B 4B

[0101] As can be seen from the above table, the visible light transmittance of the coating of Comparative Example 1 is significantly reduced compared with that of Example 1. Although the water contact angle and oil contact angle of the coating have increased to a certain extent, the light transmittance in the visible light region has decreased. The experimental phenomenon can show that excessive nano-silica filler will greatly affect the transmittance of the coating, and there is no excessive enhancement in the hydrophobic and oleophobic properties of the coating. In summary, the addition amount of nano-silica should be controlled within a reasonable range, and the performance is best when the addition amount is 4.5wt%.

[0102] The coating of Comparative Example 2 actually increases the solid content of the coating. After the same spraying process as Example 1, the coating thickness is greater, which will increase the optical path, cause more refraction, and cause a sharp decrease in the transmittance of the coating. In summary, the coating product has the best performance when the solvent content is 69.5wt%.

[0103] In summary, the quick-drying transparent super-hydrophobic and oleophobic coating provided by the present invention comprises nano-scale hydrophobic silica particles and fluorine-containing acrylic polymers; by rationally designing and combining nanoparticles and polymers, a super-hydrophobic and oleophobic coating with high visible light transmittance and excellent self-cleaning performance is obtained. The coating can ensure the cleanliness of the surface glass of the photovoltaic panel for a long time, be hydrophobic and oleophobic, maintain a high sunlight incidence rate, and improve the power generation level; at the same time, the preparation process of the coating is simple, the process is simple, and the curing film forming time is short, which reduces the cost waste caused by complex procedures and manual maintenance and cleaning.

[0104] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels, characterized in that: The coating, in terms of mass percentage, comprises: 4-5wt% hydrophobic fumed nano-silica; 24-25wt% hexafluoropropylene dimer; 55-65wt% tetrafluoroethyl ether; 0.5-3wt% methyl methacrylate; 1-2wt% hydroxyethyl methacrylate; 6-10wt% perfluorooctyl ethyl acrylate; 2-3.5wt% allyl alcohol glycidyl ether; 0.1wt% azobisisobutyronitrile; 0.2wt% perfluorooctyl ethyl iodide; 1wt% isobornyl acrylate.

2. The quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to claim 1, characterized in that: The coating, in terms of mass percentage, comprises: 4-5wt% hydrophobic fumed nano-silica; 24.5wt% hexafluoropropylene dimer; 55wt% tetrafluoroethyl ether; 2wt% methyl methacrylate; 1-2wt% hydroxyethyl methacrylate; 6-10wt% perfluorooctyl ethyl acrylate; 2-3.5wt% allyl alcohol glycidyl ether; 0.1wt% azobisisobutyronitrile; 0.2wt% perfluorooctyl ethyl iodide; 1wt% isobornyl acrylate.

3. The quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to claim 1, characterized in that: The coating, in terms of mass percentage, comprises: 4.5wt% hydrophobic fumed nano-silica; 24.5wt% hexafluoropropylene dimer; 55wt% tetrafluoroethyl ether; 2wt% methyl methacrylate; 1.7wt% hydroxyethyl methacrylate; 8wt% perfluorooctyl ethyl acrylate; 3wt% allyl alcohol glycidyl ether; 0.1wt% azobisisobutyronitrile; 0.2wt% perfluorooctyl ethyl iodide; 1wt% isobornyl acrylate.

4. The quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to any one of claims 1 to 3, characterized in that: The particle size of the hydrophobic gas-phase nano-silica is 5 to 40 nm.

5. The method for preparing a quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to any one of claims 1 to 3, characterized in that: include, Hydrophobic fumed nano-silica is dispersed in hexafluoropropylene dimer, and wet-milled after continuous stirring, and then ultrasonicated for 8 to 15 minutes to obtain solution A; Methyl methacrylate, hydroxyethyl methacrylate, perfluorooctyl ethyl acrylate, and allyl alcohol glycidyl ether are dissolved in tetrafluoroethyl ether, and stirred continuously until fully dissolved to obtain solution B; Solution A is slowly added to solution B with continuous stirring, azobisisobutyronitrile is slowly added and stirred for reaction for 10 to 20 minutes, perfluorooctyl ethyl iodide and isobornyl acrylate are added dropwise, and stirring is continued for reaction for 4.5 to 6 hours to obtain a quick-drying transparent super hydrophobic and oleophobic coating.

6. The method for preparing a quick-drying transparent super-hydrophobic and oleophobic coating suitable for photovoltaic panels according to claim 5, characterized in that: During the wet grinding process, hexafluoropropylene dimer is appropriately added to keep the total volume of the solvent unchanged.

7. The method for preparing a quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels according to claim 5, characterized in that: The continuous stirring has a stirring speed of 550 to 700 rpm and a stirring time of 5 to 30 min.

8. The method for preparing a quick-drying transparent super-hydrophobic and oleophobic coating suitable for photovoltaic panels according to claim 5, characterized in that: The stirring reaction has a stirring speed of 600-800 rpm and a stirring temperature of 30-40°C.

9. The use of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels as claimed in any one of claims 1 to 3, characterized in that: include, The quick-drying transparent super hydrophobic and oleophobic coating and the fluorinated curing agent are mixed and stirred for 5 to 15 minutes, and then applied to the surface of the photovoltaic panel. After curing for 3 to 8 minutes, a quick-drying transparent super hydrophobic and oleophobic coating is formed on the surface of the photovoltaic panel.

10. The use of the quick-drying transparent super hydrophobic and oleophobic coating suitable for photovoltaic panels as claimed in claim 9, characterized in that: The preparation method of the fluorinated curing agent, include, In a nitrogen atmosphere, hexamethylene diisocyanate trimer is added to butyl acetate, and after stirring for 20 to 40 minutes, perfluorohexylethyl alcohol is added dropwise for 20 to 40 minutes, and then the system is heated to 55 to 65°C, and stirring is continued for 1 to 3 hours, and then the final product is subjected to low-pressure rotary evaporation to remove the ethyl acetate solvent to obtain a fluorinated curing agent; Wherein, the mass ratio of the hexamethylene diisocyanate trimer to perfluorohexylethyl alcohol is 2-3:1.5-2.5.

Citation Information

Patent Citations

  • Film coating method for photovoltaic self-cleaning glass

    CN109796137A

  • Photovoltaic self-cleaning dustproof anti-reflective nano coating and use method thereof

    CN115873430A

Cited By

  • Super-hydrophobic self-cleaning coating for photovoltaic panel and preparation method of super-hydrophobic self-cleaning coating

    CN121991567A